Challenging Diagnosis of Peripillous Sheaths. Issue 4 (20th May 2014) - Gnarra, Maria; Saraceni, Pierluigi; Rossi, Alfredo; Murabit, Amera; Caradonna, Emanuela; Fania, Luca; Feliciani, Claudio
Abstract Peripillous sheaths, or hair casts, are asymptomatic, white, cylindrical concretions that encircle the hair without adhering to it. They are infrequently documented in the literature, are often misdiagnosed, and generate avoidable apprehension and expense for parents and caregivers. Dermoscopy is the standard for a rapid, noninvasive, cost‐effective diagnosis. We describe a case of peripillous sheaths presenting in a boy.